2009
DOI: 10.1897/08-302.1
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and biotransformation of structurally diverse brominated flame retardants in zebrafish (Danio rerio) after dietary exposure

Abstract: Zebrafish (Danio rerio) were fed a diet containing a mixture of 11 structurally diverse brominated flame retardants (BFRs) at nominal concentrations of either 1 or 100 nmol/g for up to 42 d, followed by an elimination period of 14 d. Uptake rates and elimination constants for five of the BFRs were calculated from measurements of their concentrations in the male fish during the exposure and elimination phases. Observed uptake efficiencies were highest for 2,4,4'-tribromodiphenyl ether (BDE 28) and 1,2-dibromo-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 28 publications
7
45
0
Order By: Relevance
“…The absence of BDE-209 in fish specimens is generally explained by the combined effects of lower bioavailability associated with its high octanol-water partition coefficient (log K ow ¼ 12.1) and its high molecular weight (m/z ¼ 959 amu) (Stapleton et al, 2004b(Stapleton et al, , 2006. However, in contrast to earlier reports, several recent studies have detected BDE-209 in some wild and experimental fish (Munschy et al, 2011;Nyholm et al, 2009;Wan et al, 2013). The reason of detecting different levels of BDE-209 may be due to the different efficiencies of uptake, elimination and metabolism for BDE-209 among various fish species.…”
Section: Pbde Congener Profiles In the Brain Compared With Other Tissuesmentioning
confidence: 93%
See 1 more Smart Citation
“…The absence of BDE-209 in fish specimens is generally explained by the combined effects of lower bioavailability associated with its high octanol-water partition coefficient (log K ow ¼ 12.1) and its high molecular weight (m/z ¼ 959 amu) (Stapleton et al, 2004b(Stapleton et al, , 2006. However, in contrast to earlier reports, several recent studies have detected BDE-209 in some wild and experimental fish (Munschy et al, 2011;Nyholm et al, 2009;Wan et al, 2013). The reason of detecting different levels of BDE-209 may be due to the different efficiencies of uptake, elimination and metabolism for BDE-209 among various fish species.…”
Section: Pbde Congener Profiles In the Brain Compared With Other Tissuesmentioning
confidence: 93%
“…The reason of detecting different levels of BDE-209 may be due to the different efficiencies of uptake, elimination and metabolism for BDE-209 among various fish species. Laboratory studies have reported the uptake efficiencies of BDE-209 were 1.4% ± 0.9% for juvenile common sole (Munschy et al, 2011), 0.62% for zebrafish (Nyholm et al, 2009), 0.44% for rainbow trout (Stapleton et al, 2006), and 0.5% ± 0.2% for Chinese sturgeon (Wan et al, 2013), respectively. In vitro metabolism studies also revealed that 65.6% of BDE-209 was biotransformed in liver microsomes of Chinese sturgeon which was lower than those in rainbow trout and common carp.…”
Section: Pbde Congener Profiles In the Brain Compared With Other Tissuesmentioning
confidence: 99%
“…Another potential BFR and PBDE metabolite is tribromoanisole (TBA) (Nyholm et al 2009). It was detected in all analysed eels and tissue types with the highest average concentrations of several ng g -1 ww (Table 2).…”
Section: Metabolism and Continued Uptakementioning
confidence: 99%
“…Rattfelt Nyholm et al (2009) studied the uptake of DBE-DBCH in zebrafish (Danio rerio) dietary exposed to a mixture of eleven different BFRs at concentrations of either 1 or 100 nmol/g feed for 42 days, followed by an elimination period of 14 days. They found a DBE-DBCH uptake efficiency of 60 % and estimated the half-life to be 0.9-1.3 days.…”
Section: Hazard Identificationmentioning
confidence: 99%